Penerapan Konseling Naratif Dalam Mengatasi Konsep Diri Negatif (Studi Kasus Klien "D") - Sari, Devy Ratna; Razzaq, Abdur; Marianti, Lena (Journal of Society Counseling, 2023)
This research is entitled Application of Narrative Counseling in Overcoming Negative Self-Concept (Case Study of Client "D" at the Ar-Rahman Drug Rehabilitation Center Foundation). The aim of this research is First, to find out the negative self-concept picture of client "D" at the Ar-Rahman Drug Rehabilitation Center Foundation. Second, to find out the application of narrative counseling in overcoming the negative self-concept of client "D" at the Ar-Rahman Drug Rehabilitation Center Foundation. In this research, the author used field research, a qualitative approach, and used a case study research method. Data collection tools in this research are observation, interviews and documentation. Research results, 1) client "D"'s self-concept is classified as problematic and more negative, where client "D" is easily offended when receiving criticism, easily angry, thirsty for praise, and treats other people as enemies. 2) The application of narrative counseling consists of an initial stage, middle stage, evaluation and final stage. The results after applying narrative counseling made client "D" have a new perspective on himself, client "D" was able to accept input and criticism well, was able to control emotions, understood the meaning of praise, and was also confident and able to have positive thoughts towards other people.